Sosialisasi Pemberdayaan Perempuan dalam Mendukung Usaha Mikro Kecil dan Menengah (UMKM) di Dusun Mekar Jaya RT 09 - Ahmad Yani; Trisna Waty Riza Eryani; Aji Syarif Hidayatullah; Muhammad Habibi (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Community service activities with the theme of Socialization of women's empowerment in supporting micro, small and medium enterprises (MSMEs) were carried out in Karang Tunggal Village, Mekar Jaya Hamlet, RT 09, Tenggarong Seberang District together with local mothers. The time for this activity was Saturday, December 7, 2024 at 09.00 until finished. This activity went well and received a warm and enthusiastic welcome from the participating mothers. The objectives of this community service are; (1) Through PKM, the role of women in supporting MSMEs in Karang Tunggal Village, Mekar Jaya Hamlet 09 can be identified (2) Discussion of risks and obstacles and solutions so that women can play a role in developing MSMEs in Karang Tunggal Village, Mekar Jaya Hamlet 09. The PKM activity method used was discussion and question and answer. The hope of the community service activity in the form of Socialization of women's empowerment in supporting micro, small and medium enterprises (MSMEs) of the mothers of Dusun Mekar Jaya RT.09 can provide motivation to be more involved in improving the family economy, especially through simple MSME activities and motivated to increase knowledge and insight into entrepreneurship, especially women.